Pioneering Advances and Innovative Applications of Mesoporous Carriers for Mitochondria-Targeted Therapeutics - Mohamad Anas Al Tahan; Sana Al Tahan (Frontiers Media S.A., 2024)
Mitochondria, known as the cell's powerhouse, play a critical role in energy production, cellular maintenance, and stemness regulation in non-cancerous cells. Despite their importance, using drug delivery systems to target the mitochondria presents significant challenges due to several barriers, including cellular uptake limitations, enzymatic degradation, and the mitochondrial membranes themselves. Additionally, barriers in the organs to be targetted, along with extracellular barriers formed by physiological processes such as the reticuloendothelial system, contribute to the rapid elimination of nanoparticles designed for mitochondrial-based drug delivery. Overcoming these challenges has led to the development of various strategies, such as molecular targeting using cell-penetrating peptides, genomic editing, and nanoparticle-based systems, including porous carriers, liposomes, micelles, and Mito-Porters. Porous carriers stand out as particularly promising candidates as drug delivery systems for targeting the mitochondria due to their large pore size, surface area, and ease of functionalisation. Depending on the pore size, they can be classified as micro-, meso-, or macroporous and are either ordered or non-ordered based on both size and pore uniformity. Several methods are employed to target the mitochondria using porous carriers, such as surface modifications with polyethylene glycol (PEG), incorporation of targeting ligands like triphenylphosphonium, and capping the pores with gold nanoparticles or chitosan to enable controlled and triggered drug delivery. Photodynamic therapy is another approach, where drug-loaded porous carriers generate reactive oxygen species (ROS) to enhance mitochondrial targeting. Further advancements have been made in the form of functionalised porous silica and carbon nanoparticles, which have demonstrated potential for effective drug delivery to mitochondria. This review highlights the various approaches that utilise porous carriers, specifically focusing on silica-based systems, as efficient vehicles for targeting mitochondria, paving the way for improved drug delivery strategies in mitochondrial therapies.